2014
DOI: 10.1038/srep03741
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Plasmodium falciparum malaria prevalence, genetic diversity and endemic Burkitt lymphoma in Malawi

Abstract: Endemic Burkitt lymphoma (eBL) has been linked to Plasmodium falciparum (Pf) malaria infection, but the contribution of infection with multiple Pf genotypes is uncertain. We studied 303 eBL (cases) and 274 non eBL-related cancers (controls) in Malawi using a sensitive and specific molecular-barcode array of 24 independently segregating Pf single nucleotide polymorphisms. Cases had a higher Pf malaria prevalence than controls (64.7% versus 45.3%; odds ratio [OR] 2.1, 95% confidence interval (CI): 1.5 to 3.1). C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 32 publications
3
45
1
1
Order By: Relevance
“…Research confirmed Epstein-Barr virus (EBV) as a causative organism for eBL (Rowe et al, 2014). Further studies have elucidated the roles of malaria infections and EBV in tumourigenesis (Johnston et al, 2014). BL is a highly aggressive B cell NHL associated with a translocation involving the MYC oncogene on chromosome 8.…”
Section: Haematological Cancersmentioning
confidence: 99%
“…Research confirmed Epstein-Barr virus (EBV) as a causative organism for eBL (Rowe et al, 2014). Further studies have elucidated the roles of malaria infections and EBV in tumourigenesis (Johnston et al, 2014). BL is a highly aggressive B cell NHL associated with a translocation involving the MYC oncogene on chromosome 8.…”
Section: Haematological Cancersmentioning
confidence: 99%
“…2 The ecological association between eBL and P. falciparum was shown in the 1970s, 1 but there is still limited evidence from studies examining this association at an individual level. [3][4][5][6][7][8] In 2012, the International Agency for Research on Cancer classified P. falciparum infection in holoendemic areas as "probably carcinogenic to humans." 9 A better description of eBL epidemiology is needed to enhance current understanding of the etiology of the disease.…”
mentioning
confidence: 99%
“…Endemic Burkitt lymphoma (eBL) is a B-cell non-Hodgkin lymphoma genetically characterized by a chromosomal translocation t (8,14) that results in deregulation of the c-MYC oncogene. eBL is the main pediatric cancer in equatorial Africa accounting for about 50% of childhood cancers, and 90% of lymphomas.…”
mentioning
confidence: 99%
“…Varios estudios han demostrado que la parasitemia, la prevalencia de infección por Plasmodium y algunas variantes genéticas se relacionan directamente con el desarrollo del linforma. Si bien los mecanismos biológicos y oncogénicos no se han establecido completamente, se ha identificado la activación atípica de células B de memoria cuya inducción puede estar mediada por el imbalance oxidativo propio de la infección parasitaria 8 .…”
Section: Artículo Originalunclassified